Knowledge and Practices of High School Teachers Regarding Healthy Life Style in Erbil City/Iraq - Mohammed- Tahr; Kareem Fattah Aziz (Hawler Medical University, 2023)
Background and Objective: Health promotion in a school setting involves educating the students and teachers about health-related matters that reflect on health in a more holistic way. Lifestyle includes behaviors such as food habits, sleeping and resting, physical activity and exercising, weight controlling, smoking and others. The purpose of this study is to assess the knowledge and practices of teachers about healthy lifestyles in the high school in Erbil city. Methods: A descriptive cross-sectional study was used. The data were collected from 3th December 2021 to 28th March 2022. A cluster random sampling technique was used to collect 400 teachers who attended High school in Erbil city. A valid questionnaire was used for data collection by face to face; it contained three parts of sociodemographic data, items of knowledge and practices. The validity and reliability were conducted for the tool and the value of Cronbach's Alpha was 0.826. Results: The teachers had good knowledge and practices about promoting healthy lifestyles. There was a significant association between age, education level and experience with their knowledge and practices. There was no significant association between their knowledge and gender, marital status, or economic status, and no significant association between their practices and variables like gender, marital status and economic status. Conclusion: The outcome of the study revealed that most of the teachers had good knowledge and practices regarding healthy lifestyles in high school in Erbil city /Iraq, so they might be as a source of healthy lifestyles to the public. There was significant association between knowledge, practices and their age and education level, while there was no significant association between their knowledge, practices and gender and marital status.